Simulated versus traditional therapeutic radiography placements: A randomised controlled trial. Issue 2 (May 2020) - Ketterer, S.-J.; Callender, J.; Warren, M.; Al-Samarraie, F.; Ball, B.; Calder, K.-A.; Edgerley, J.; Kirby, M.; Pilkington, P.; Porritt, B.; Orr, M.; Bridge, P.
Abstract: Introduction: Clinical placements provide rich learning environments for health professional pre-registration education but add significant workload pressure to clinical departments. Advances in simulation approaches mean that many aspects of students' clinical learning can be undertaken in the academic environment. There is, however, little data identifying specific pedagogical gains afforded by simulation compared to clinical placement. This study measured the impact of a comprehensive integrated simulation placement on student clinical skill acquisition. Methods: A virtual department was developed using a range of simulation equipment and software, with actors and service users providing a range of patients for students to engage with. A cohort of 29 first-year undergraduate therapeutic radiography students were randomly assigned to either simulated or conventional clinical placement. Clinical skills assessment scores provided by a blinded assessor were then compared. Results: Mean overall assessment scores for each cohort were within 3% of each other. The simulation cohort had over 10% higher "communication" scores than the traditional group (p = 0.028). The ability to gain both technical and interpersonal skills simultaneously improved learning compared to clinical placement. Students valued the structured approach of the simulated placement and the opportunity to practice techniques in a safe unpressured environment. Conclusion: An integrated simulated placement can help students to achieve clinical learning outcomes and lead to improved interpersonal skills. Implications for practice: Use of blended simulation resources can enable students to acquire technical, procedural and interpersonal skills which in turn may enable reduction of overall clinical placement time and departmental training burden.